Pseudoverrucous papules and nodules (PPN) in association with female epispadias and bifid clitoris: a rare presentation. - Tambe, S.; Chalvade, P.; Jerajani, H.; Singhania, P.; Singal, A. (European Journal of Pediatric Dermatology, 2014)
Pseudoverrucous papules and nodules (PPN) are an uncommon entity, mainly reported in the genital and perineal area. PPN has been reported in patients with urostomies and colostomies. It is thought to be a manifestation of chronic irritant contact dermatitis that develops as a result of prolonged exposure to liquid stool and/or urine and considered to be a part of the spectrum of erosive papulonodular dermatosis. Here we report a case of PPN associated with female epispadias in a 10-year-old little girl.